Perancangan Database Akuntansi Menggunakan Microsoft Access pada Usaha Konveksi Taylor Abadi - Wiwik Andriani; Eka Rosalina; Fera Sriyunianti; Ferdi Afrizon; Dandi Aprila (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2023)
This service aims to help design accounting applications at the Konveksi Taylor Abadi Convection Business using Microsoft Access. The application is designed according to the needs of the store, where this application has a form that is equipped with Visual Basic for Application (VBA) and other facilities such as an account list form, inventory list, fixed asset list, transaction recording consisting of sales, purchases, raw material usage, allocation forms. factory overhead costs, direct labor costs, finished production or finished products. This application provides financial reports ranging from reports on the cost of production, profit and loss reports, reports on changes in capital, balance reports and cash flow reports as well as other data needed by the company. From the results of this service, it was found that there were deficiencies in the recording and financial reports at Taylor Abadi Convection. Therefore, the author provides a solution for Konveksi Taylor Abadi Convection to use Microsoft Access computer applications in recording transactions and preparing financial reports in accordance with Financial Accounting Standards (SAK) quickly and automatically.